Accounting, Statistics Bakhtigozina E. I. Assessing the System of Internal Control on the Basis of the Risk Card - E. I. Bakhtigozina (Вестник Российского экономического университета имени Г. В. Плеханова, 2018)
Efficiency of managerial decisions, higher economical characteristic of transactions, providing truthfulness of finance accounting, compliance of company work with the effective legislation depend greatly on competent internal control. Lately serious attention has been paid to the function of internal control in the organization. It is connected with the fact that Russian companies are more and more involved in global integration and economic processes. Shaping the system of internal control implies identification of the most serious risks, i.e. those which can cause finance losses, designation of control procedures in order to minimize or eliminate risks. The article investigates issues of developing and estimating the system of internal control on the basis of risk card by singling out one of the principle elements of the system – risk estimation. The author shows key stages of work in the field of building the effective system of internal control: identification and description of key business processes; definition and identification of risks typical of key business processes; estimation of risks; finding borders of risk acceptability; disclosing information about identified risks; development and introduction of effective control measures aimed at risk control beyond borders of acceptability. Execution of the mentioned above steps could provide efficiency of the system of internal control that is efficiency of managerial decisions promoting favorable development of finance and economic activity.